Comparison of oncologic outcomes between open and laparoscopic distal pancreatectomy for pancreatic ductal adenocarcinoma using data from the KOTUS-BP national database: overcoming selection bias and the necessity of definite indications. Issue 10 (October 2022) - Kim, Hongbeom; Heo, Jin Seok; Kang, Chang Moo; Hwang, Ho Kyoung; Han, Ho-Seong; Yoon, Yoo-Seok; Park, Joon Seong; Han, Sung-Sik; Kim, Yong Hoon; Lee, Hyeon Kook; Yu, Young-Dong; Choi, In Seok; et al.
Abstract: Background: Despite the lack of high-level evidence, laparoscopic distal pancreatectomy (LDP) is frequently performed in patients with pancreatic ductal adenocarcinoma (PDAC) owing to advancements in surgical techniques. The aim of this study was to investigate the long-term oncologic outcomes of LDP in patients with PDAC via propensity score matching (PSM) analysis using data from a large-scale national database. Methods: A total of 1202 patients who were treated for PDAC via distal pancreatectomy across 16 hospitals were included in the Korean Tumor Registry System-Biliary Pancreas. The 5-year overall (5YOSR) and disease-free (5YDFSR) survival rates were compared between LDP and open DP (ODP). Results: ODP and LDP were performed in 846 and 356 patients, respectively. The ODP group included more aggressive surgeries with higher pathologic stage, R0 resection rate, and number of retrieved lymph nodes. After PSM, the 5YOSRs for ODP and LDP were 37.3% and 41.4% ( p = 0.150), while the 5YDFSRs were 23.4% and 27.2% ( p = 0.332), respectively. Prognostic factors for 5YOSR included R status, T stage, N stage, differentiation, and lymphovascular invasion. Conclusion: LDP was performed in a selected group of patients with PDAC. Within this group, long-term oncologic outcomes were comparable to those observed following ODP.